2018
DOI: 10.1093/jncics/pky073
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behaviors, TV Viewing Time, and Risk of Young-Onset Colorectal Cancer

Abstract: Background Colorectal cancer (CRC) diagnosed before age 50 years, or young-onset CRC, is increasing globally with undefined etiology. A sedentary lifestyle is an emerging risk factor for CRC after age 50 years, but its role in young-onset CRC is unknown. Methods We prospectively evaluated sedentary behaviors, primarily time watching television (TV), and risk of young-onset CRC among 89 278 women in the Nurses’ Health Study II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 60 publications
5
100
1
Order By: Relevance
“…adults have increased in parallel to the increase in EOCRC, and an independent relationship is yet to be clearly demonstrated.Nguyen et al, has recently reported a significant association between increased risk of EOCRC and sedentary TV watching time after adjusting the persumed risk factors such as lack of exercise and obesity[105]. Additionally, there is a consistent relationship between type 2 diabetes and CRC, and this is likely to be more pronounced in young adults under 55 years[106].…”
mentioning
confidence: 99%
“…adults have increased in parallel to the increase in EOCRC, and an independent relationship is yet to be clearly demonstrated.Nguyen et al, has recently reported a significant association between increased risk of EOCRC and sedentary TV watching time after adjusting the persumed risk factors such as lack of exercise and obesity[105]. Additionally, there is a consistent relationship between type 2 diabetes and CRC, and this is likely to be more pronounced in young adults under 55 years[106].…”
mentioning
confidence: 99%
“…In our study, most patients reported a moderate and low level of physical activity, accounting for almost 83% of the total patients. [18][19][20][21] Regarding fat status, although BMI is not a reliable indicator of fat loading, in our study, most patients diagnosed with CRC were overweight(29%) and obese(53%) ( Table 3). Smoking is considered a "universal carcinogen", recent research showing a link between nicotine consumption and CRC development.…”
Section: Resultsmentioning
confidence: 60%
“…A number of studies highlighted the correlations between cancer risk and extrinsic factors such as specific dietary habits (non-Mediterranean Western diet, HFD, processed meat, alcohol consumption), sedentary lifestyle, environmental pollution and urbanization [27][28][29][30]. In particular, the adoption of WSD in both industrialized and developing countries is linked to higher obesity rates and prevalence of diabetes, cardiovascular disease and cancer, with a specific association between obesity and CRC [31].…”
Section: Correlating Diet Intestinal Homeostasis and Colorectal Cancmentioning
confidence: 99%
“…Potential culprits are represented by cesarean delivery, absence of breastfeeding, prenatal/perinatal/infancy antibiotic use (which impacts the health of the gut microbiota) and changes in childhood diet [71]. Sedentary lifestyle during childhood, and specifically TV viewing time, has been also correlated with an increasing risk of EO-CRC [29] (Figure 1). In light of these findings, future strategies against EO-CRC must include a combined effort of epidemiological, basic and clinical research together with informative campaigns and socioeconomic measures.…”
Section: Increased Crc Incidence In the Young Adult Population: Molecmentioning
confidence: 99%